First record of Odontomesa Pagast from China, with description of the immature stages of O. ferringtoni Sæther (Diptera, Chironomidae, Prodiamesinae) - Liu, Wenbin; Ferrington, Leonard C. Jr; Wang, Xinhua (Zootaxa, 2016)
The genus Odontomesa Pagast is newly recorded from China. Based on associated material collected from China and U.S.A, the immature stages of Odontomesa fulva (Kieffer) and Odontomesa ferringtoni Sæther are redescribed. Odontomesa sp. A Sæther is confirmed as conspecific with O. ferringtoni. The generic diagnosis of immature stages is emended. Keys to the known larvae and pupae of the genus are presented.